Population Ecology Of Brown Planthopper (Nilaparvata Lugens Stal) And White Backed Planthopper (Sogatella Furcifera Horvath) In Myanmar - San, San Win (2010)

(untitled)
The ecological studies on the brown planthopper (BPH) Nilaparvata lugens (Stal) (Hemiptera: Homoptera) and the white backed plant hopper (WBPH) Sogatella furcifera (Horvath) (Hemiptera: Homoptera) were carried out in Myanmar. BPH is one of the major pests of rice and damage by this pest could cause hopper burns due to intensive sucking of the plant. This suggested an urgent need for alternative control measures besides using chemical insecticides. This study was conducted with the objectives to establish the biological life tables of BPH and WBPH, investigate their feeding and movement behaviours and examine the relationships between population fluctuations, host plant, rainfall and humidity in the field. The studies were conducted in an unsprayed rice field at Hmawbe Research Area, Myanmar from July 2007 to May 2008. Age specific survival and fecundity rates of BPH and WBPH were measured under field conditions. A life table was constructed using single sex methods. The population parameters of BPH fed on rice showed that the intrinsic rate of natural increase (rm) of BPH was 0.0677 per female per day. The daily finite rate of increase (λ) was 1.07 females per female per day with mean generation time (T) of 34.64 days. The net reproduction rates (Ro) of the population was 10.02. The population doubling in time (DT) was within 10.42 days. The population parameter of WBPH fed on rice showed that the intrinsic rate of natural increase (r m) of WBPH were 0.0699 per female per day. The daily finite rate of increase (λ) was 1.0255 females per female per day with mean generation time (T) of 34.97. The net reproduction rates (Ro) of the population was 9.2732. The population doubling time (DT) was within 10.88 days. Feeding behaviour studies suggested that in both choice and no choice experiments, the patterns of feeding lesions between BPH and WBPH were quite similar. Higher numbers of feeding lesions were observed on 30 day old plants than 45 day and 60 days old plants. More feeding on leaf sheath than on leaf blade was observed for both planthoppers. In the movement behaviour study, it was revealed that BPH adults were found to be more active than the nymphal instars. In older rice plants, the highest movement (4.7 cm per two hours) was observed on 60- day-old plants and lowest (2.7 cm per two hours) on 30-day-old plants. Increased movements of planthoppers were observed at 13:00hrs. Population fluctuation study revealed that BPH population was high at 64 and 74 DAT (in mid September 2007) associated with heavy rainfall, high temperature and high humidity. The population was lowest at 138 DAT (in the mid week of October 2007) suggesting that low rainfall and low humidity were, at least partially responsible for the decrease population of the BPH. During the dry season, the population was low at 8 DAT (early week of January 2008) and then increased at 31 DAT (first week of February 2008). However, the population declined at 56 DAT and increased to moderate numbers at 86 DAT. The population development trend of WBPH was almost similar to those observed for BPH. During the dry season, the highest WBPH population was recorded at 90 DAT and the lowest at 33 DAT. During the first cropping coinciding with the rainy season, the fluctuation of planthoppers was correlated with temperature and rainfall. During the second cropping coinciding with the dry season, there was no rainfall and planthoppers population was observed to be correlated to temperature and relative humidity. Therefore, temperature, rainfall and relative humidity influenced planthopper populations during two different rice growing seasons.